2019
DOI: 10.7554/elife.49494
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophins induce fission of mitochondria along embryonic sensory axons

Abstract: Neurotrophins are growth factors that have a multitude of roles in the nervous system. We report that neurotrophins induce the fission of mitochondria along embryonic chick sensory axons driven by combined PI3K and Mek-Erk signaling. Following an initial burst of fission, a new steady state of neurotrophin-dependent mitochondria length is established. Mek-Erk controls the activity of the fission mediator Drp1 GTPase, while PI3K may contribute to the actin-dependent aspect of fission. Drp1-mediated fission is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 73 publications
(194 reference statements)
1
47
0
Order By: Relevance
“…Emerging evidence suggests that neurotrophins have also been involved in directing axonal and dendritic arborization, formation of dendritic spines and functional synaptic connections, as well as release of neurotransmitters [ 65 , 66 , 67 ], which together shapes the architecture of neural networks in the adult. We found that encapsulated NGF promoted branching of neurites in local hippocampal neurons, which subsequently established functional synapses on neighbouring cells at a comparatively early stage in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that neurotrophins have also been involved in directing axonal and dendritic arborization, formation of dendritic spines and functional synaptic connections, as well as release of neurotransmitters [ 65 , 66 , 67 ], which together shapes the architecture of neural networks in the adult. We found that encapsulated NGF promoted branching of neurites in local hippocampal neurons, which subsequently established functional synapses on neighbouring cells at a comparatively early stage in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Axon-TRAP experiments have further identified that lamin B2 (LB2) mRNA is translated in axons and inhibition of local LB2 synthesis impairs mitochondrial fission and axon health during development (Yoon et al, 2012). Mitochondrial fission at nascent axon branch points also provides the ATP necessary for local translation of proteins that regulate actin remodeling and axon branching (Spillane et al, 2012(Spillane et al, , 2013Lewis et al, 2018;Armijo-Weingart et al, 2019).…”
Section: Local Transcriptomes/translatomes Are Remodeled During Circumentioning
confidence: 99%
“…Inhibition of OxP prevents branching along sensory axons in response to nerve growth factor (NGF; Spillane et al., 2013). Although stalled mitochondria determine the sites of axons where branching may occur, following the initial maturation of a branchlet mitochondria undergoing transport then populate the branch as it develops further (Armijo‐Weingart et al., 2019). Developing branches are preferentially populated by mitochondria representing the shorter subpopulation of axonal mitochondria (Armijo‐Weingart et al., 2019).…”
Section: Mitochondria and Oxidative Phosphorylationmentioning
confidence: 99%
“…Although stalled mitochondria determine the sites of axons where branching may occur, following the initial maturation of a branchlet mitochondria undergoing transport then populate the branch as it develops further (Armijo‐Weingart et al., 2019). Developing branches are preferentially populated by mitochondria representing the shorter subpopulation of axonal mitochondria (Armijo‐Weingart et al., 2019). In the case of NGF induced sensory axon branching NGF drives a rapid bout of mitochondria fission and then maintains a new steady state of shorter mitochondria in axons that provide a greater number of ideally sized mitochondria for branch development (Armijo‐Weingart et al., 2019).…”
Section: Mitochondria and Oxidative Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation